PEMBERDAYAAN MASYARAKAT UNTUK MEMBERIKAN PILIHAN PELUANG USAHA MANDIRI BAGI KELOMPOK KOMISI KAUM WANITA GSJA MARANATHA - MALANG - Tri Istining Wardani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2018)
The purpose of this community service is to empower the hidden potential and creativity in the community, which in this case is to improve and develop an entrepreneurial culture for the core members of a household, especially for the Women's Commission in GSJA Maranatha Malang.This community empowerment activity will be divided into two modules, the first is by providing theoretical debriefing about the objectives, benefits and tips for running entrepreneurial activities, as well as the importance of running an independent business for a woman to improve family welfare. While the second module is by providing basic knitting practice as an option to run an independent business. Basic training to produce knitting products using crochet technique, processing yarn by forming twigs with the help of one hook / needle / songket / hook / hakken / hakpen and the overall result of forming a new object or material. Based on the results of the training evaluation, it can be concluded that the training runs smoothly and effectively because the target audience can absorb the knowledge conveyed and are able to produce finished products according to the target from the beginning.